Unmuting musical instruments held in ethnographic collections: towards a sound remediation? - Louis Petitjean (Museum, Materials and Discussions)
This paper explores the integration of sound in ethnographic museums displays as a possible way to deal with the mediation of musical instruments taken from colonised cultures. It examines museums’ evolving approaches to decolonisation, particularly the incorporation of multi-sensory experiences that allow audiences to connect with heritage beyond visual displays. Museums like the Musée du Quai Branly – Jacques Chirac, the case study of the article, attempt to address historical erasures by working with artists to create installations that let musical instruments resonate differently. By shifting the focus from preservation alone to collaborative, sensory engagements, these museums aim to repair dissonant heritages, fostering inclusivity and rethinking representation within modern museology.